47 INCREASED NOX1 IN NEOINTIMAL SMOOTH MUSCLE CELLS IS ASSOCIATED WITH REDOX-SENSITIVE SIGNALING AND ACTIVATION OF MATRIX METALLOPROTEINASE 9. (1st March 2006) - Xu, S.; Jagadeesha, D.; Chamseddine, A.; Bhalla, R.; Miller, F.
Abstract : The vascular response to injury involves redox-dependent activation of smooth muscle cells (SMC) and development of a neointima. Activation of matrix metalloproteinase 9 (MMP-9) appears to be critical in the development of arterial lesions. We hypothesized that increased NADPH oxidase-derived superoxide (O2 2 ) by neointimal SMC contributes to activation of MMP-9. Two weeks after balloon injury of rat aorta, neointimal SMC showed higher O2 - levels compared with adjacent medial SMC. A role for NADPH oxidase was suggested by the observations that neointimal SMC O2 - levels were reduced by the flavoenzyme inhibitor DPI, and immunostaining for p47phox and p22phox were increased in the neointimal, as compared with medial, SMC. Neointimal and medial SMC were isolated and grown in culture. Consistent with the findings in situ, O2 - levels and NADPH oxidase activity were significantly greater in neointimal SMC. Nox1 mRNA levels were more than 2-fold increased in neointimal SMC, whereas Nox4 expression was similar to that of medial SMC. ERK1/2 kinase activation was greater in neointimal vs medial SMC and was inhibited by tiron and DPI. MMP-9 activity, as measured by gelatin zymography, was higher in neointimal SMC compared to medial SMC in basal conditions and 48 hours after IL-1b stimulation and was reduced by pretreatment with the ERK inhibitor PD98059 or DPI. We conclude that NADPH oxidase-derived O2 - signals activation of MMP-9 following vascular injury. Moreover, Nox1-dependent cell signaling in neointimal SMC may play an important role in the pathogenesis of vascular disease. Supported by AHA and NIH 14388 and HL081750.